2020
DOI: 10.3390/cells9081807
|View full text |Cite|
|
Sign up to set email alerts
|

Fyn Tyrosine Kinase Elicits Amyloid Precursor Protein Tyr682 Phosphorylation in Neurons from Alzheimer’s Disease Patients

Abstract: Alzheimer’s disease (AD) is an incurable neurodegenerative disorder with a few early detection strategies. We previously proposed the amyloid precursor protein (APP) tyrosine 682 (Tyr682) residue as a valuable target for the development of new innovative pharmacologic or diagnostic interventions in AD. Indeed, when APP is phosphorylated at Tyr682, it is forced into acidic neuronal compartments where it is processed to generate neurotoxic amyloid β peptides. Of interest, Fyn tyrosine kinase (TK) interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 73 publications
4
47
0
Order By: Relevance
“…Our group have previously underlined the crucial role of APP Tyr 682 residue in the processes responsible for the generation of Aβ peptides in human neurons [ 2 , 3 ]. APP Tyr 682 residue is located in the highly conserved 682 YENPTY 687 motif, which binds specific adaptor proteins depending on its phosphorylation/dephosphorylation state [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our group have previously underlined the crucial role of APP Tyr 682 residue in the processes responsible for the generation of Aβ peptides in human neurons [ 2 , 3 ]. APP Tyr 682 residue is located in the highly conserved 682 YENPTY 687 motif, which binds specific adaptor proteins depending on its phosphorylation/dephosphorylation state [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, APP accumulates in the acidic neuronal compartments, such as late endosomes and lysosomes, where it is preferentially cleaved to generate Aβ peptides [ 3 ]. Notably, we previously showed that high levels of phosphorylation of APP Tyr 682 residue in neurons differentiated from neuronal stem cells of AD patients [ 2 , 3 , 10 ] preceding Aβ accumulation, and promoting neuronal degeneration. We therefore suggested that this high levels of APP Tyr 682 phosphorylation might be an early marker of neuronal degeneration [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations